Pembentukan Kepribadian Diri Yang Pro-Lingkungan Berbasis pada Prinsip-Prinsip Akhlak Tasawuf - Khoir, Muhammad Romizan; Arsyadani, Ahmad Syifa; Isnawati, Zakiyah; Hidayatullah, Ahmad Fauzan (Aqlania, 2023)
Pro-Environmental Self-Personality is a concept that refers to the level of concern and responsibility for the environment. Pro-environmental behavior is an individual action in an effort to protect the environment or minimize the impact of environmental damage, as well as improve environmental conditions. Factors influencing pro-environmental behavior include knowledge, attitudes, motivations, effectiveness of consumer perception, childhood experiences, knowledge and education, personality, locus control, and awareness of pro-environmental behavior. Pro-environmental approaches shape behaviors that aim to preserve nature, such as energy saving, mobility and transportation, waste prevention, recycling, consumerism, and behaviors aimed at preserving nature The formation of pro-environmental behavior must be done early so that it can become a habit in life. Without a pro-environmental approach, the formation of a good personality will be impossible. The moral principles of Sufism are one approach that can be used to form a good and pro-environment personality. In this article, we will elaborate on the formation of a pro-environment personality based on the moral principles of Sufism.